Comparison of Amiodarone with Combined Doses of Magnesium Sulphate and Lidocaine for Prevention of Ventricular Fibrillation Following Coronary Clamp Release During Coronary Artery Bypass Graft Surgery - Akram, Muhammad Adnan; Naseer, Mehwish; Fayaz, Fakher-e-; Khurshid, Hana; Ali, Nasir; Chaudhry, Imtiaz Ahmed (Pakistan Armed Forces Medical Journal, 2022)
Objective: To compare the effects of amiodarone with effects of combined doses of magnesium sulphate and lidocaine for prevention of ventricular fibrillation following coronary clamp release during (coronary artery bypass grafting) CABG.Study Design: Comparative cross sectional study.Place and Duration of Study: Army Cardiac Centre, Lahore Pakistan, from Jun 2021 to Dec 2021.Methodology: One hundred patients who reported at Army Cardiac Centre Lahore, Pakistan for coronary artery bypass grafting surgery, were involved in comparative study. Patients satisfying the inclusion criteria were allocated into the LM(Lidocaine Magnesium) and A (Amiodarone) groups. Following aortic cross clamp release, the incidence of ventricular fibrillation (VF) and other arrhythmias was calculated in first 30 minutes and up to 24 hours later. The ionotropic agent used was epinephrine at a rate of 0.05 to 0.1 micrograms/kg/minute. Within 15 minutes of anesthetic induction and 15 minutes after the CPB pump was removed, hemodynamic parameters were assessed and recorded.Results: Arrhythmias within 30 minutes and up to 24 hours after aortic cross clamp ACC release in A and LM group were compared. The difference between two groups, having arrhythmias and no arrhythmias was statistically insignificant (p≥0.050) except VF up to 24 hours after ACC release. The highest voltage for defibrillation was used in Group-A n=20 (40.0%) and n=27 (54.0%) in L.M group, (p=0.004). The average electrical defibrillations in group-A was less than that of group L.M,(p=0.000). While, the use of ionotropic agent was almost equal in both the groups, (p=0.975).Conclusion: Overall, the amiodarone group had a decreased incidence of VF when the ACC was released, while the difference was not statistically significant.